Static and dynamic analysis of a bistable plate under nonlinear magnetic force. (April 2022) - Habibzadeh, Negin; Tikani, Reza; Ziaei-Rad, Saeed; Taki, Mohammad Sina
In this article, bistable laminates are statically and dynamically studied under the existence of nonlinear magnetic force. The bistable laminates with magnetic forces are considered as a nonlinear system for vibration energy harvesting. First, a semi-analytical model was established based on the energy approach for the bistable plate together with magnets. The magnetic force versus distance was measured, and then, an equation was fitted to the experimental data. The damping of the whole system was determined experimentally, and Rayleigh damping coefficients were extracted and used in all models. Next, a finite element model of the whole system was developed to compute the dynamic response of the system under different base excitations. Finally, a test rig was constructed, and the system responses were measured under various base excitations. The dynamic snap-through of the bistable laminate under magnetic forces was also measured and compared with the results obtained from the semi-analytical and finite element model. The analysis shows that adding a magnetic force will reduce the amplitude of base excitation that is needed for dynamic snap-through for %28.6. The analysis shows that the bistable plate with a magnetic force can be a good candidate for energy harvesting because the nonlinear magnetic forces under certain conditions reduce the snap-through force and consequently increase the harvested energy. This is because of the fact that the presence of the magnetic forces allows the system to vibrate between its two stable configurations under lower base excitation amplitudes.